(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
According to Bonaventure, theological reasoning requires grace in order to arrive at wisdom, namely knowledge and love. This shows that there is an integral relationship between theology and spirituality. Spirituality is used as the basis for theological reflection. In other words, theology begins with the spiritual life. Theology directs humans to meet God and manifest love in everyday life. So that theology cannot be reduced only as an intellectual thought. In addition, reason must be equipped with faith in order to reach perfection and enable humans to understand reality correctly. Bonaventure’s contemplative method directs humans to transcend the limitations of logic and reason.